Dojenje in tandemsko dojenje - Merše Lovrinčević, Katarina (Obzornik zdravstvene nege, 2018)
Introduction: Tandem breastfeeding is a poorly understood concept. Mothers who tandem breastfeed are often faced with social stigma and poor support given by healthcare professionals. The purpose of the research was to study the knowledge on tandem breastfeeding among students of nursing. Methods: The research is based upon quantitative explorative-nonexperimental descriptive research design. Participants were random nursing (n = 66) and dietetics (n = 24) students. Data were gathered with a structured questionnaire (Cronbach % = 0.914). Descriptive statistics were used; a chi square test and singlefactor analysis of variance. Results: 50.7 % (n = 36) women and 84.2 % (n = 16) men (%2 = 6.898, p = 0.009) considered it physiologically normal that if a woman stops breastfeeding the older child when she becomes pregnant again. 79.2 % (n = 19) dietetics students compared to 54.5 % (n = 36) nursing students (%2 = 4.489, p = 0.034) knew that breastfeeding was the only form of nutrition in the first six months of an infant%s life. 86.3 % (n = 44) women in comparison to 13.7 % (n = 7) men recognized that the statement that infants who are tandem breastfed experience slower growth, was incorrect. Discussion and conclusion: Students participating in the research have demonstrated a lack of knowledge in both, breastfeeding and tandem breastfeeding. The study programme should contain more content on breastfeeding.
Keywords: assistance with breastfeeding; medicinske sestre; nurses; podpora; pomoč pri dojenju; sočasno dojenje sorojencev; student; students; support; študenti; tandem breastfeeding